Association of VEGF genetic polymorphisms with recurrent spontaneous abortion risk: a systematic review and meta-analysis. - Xinghua Xu; Chigang Du; Huihui Li; Jing Du; Xue Yan; Lina Peng; Guangyao Li; Zi-Jiang Chen (PLoS ONE, 2015)
Background Studies of the associations between the genetic polymorphisms of the vascular endothelial growth factor (VEGF) gene and recurrent spontaneous abortion (RSA) have revealed conflicting results. The present meta-analysis was performed to provide a more precise estimation of these relationships and to explore potential sources of heterogeneity that may have influenced the reported disparities. Methods An extensive literature search for relevant studies was conducted on PubMed, Embase, and The Cochrane Library through June 6, 2014. Crude odds ratio (OR) with 95% confidence intervals were calculated. Results 10 case-control studies including 1,832 RSA patients and 2,271 healthy controls were identified. Meta-analysis indicated that rs1570360, rs3025039, rs2010963, and rs3025020 polymorphisms in the VEGF gene correlated with elevated RSA risk. The rs1570360 variant was statistically significantly relevant to RSA risk among non-Asian populations. Interestingly, the rs3025039 variant was statistically significantly relevant to RSA risk among Asian populations. Conclusions The current meta-analysis indicates that rs1570360, rs3025039, rs2010963, and rs3025020 polymorphisms increase RSA susceptibility. Moreover, rs1570360 and rs3025039 polymorphisms may play various roles in RSA susceptibility in various geographic groups.